3 Tesla sodium inversion recovery magnetic resonance imaging allows for improved visualization of intracellular sodium content changes in muscular channelopathies - Nagel, Armin Michael; Amarteifio, Erick; Lehmann-Horn, Frank; Jurkat-Rott, Karin; Semmler, Wolfhard; Schad, Lothar R.; Weber, Marc-André (Investigative radiology, 2011)
Objectives: - To implement different sodium (23Na)-magnetic resonance imaging (MRI) contrasts at 3 Tesla and to evaluate if a weighting toward intracellular sodium can be achieved, using 2 rare muscular channelopathies as model diseases. - Materials and Methods: - Both lower legs of 6 patients with hypokalemic periodic paralysis (HypoPP), 5 patients with paramyotonia congenita (PC), and 5 healthy volunteers were examined on a 3 Tesla system with 3 different 23Na-MRI pulse sequences. HypoPP and PC are rare muscle diseases, which are well characterized by elevated myoplasmic sodium at rest and after cooling, respectively. Intra- and interindividual comparisons were performed before and after provocation of one lower leg muscle. Three different 23Na-MRI sequences were applied: (i) The total tissue sodium concentration was measured using a spin-density sequence (23Na-TSC). (ii) A T1-contrast was applied to assess whether the known changes of the intracellular sodium concentration can be visualized by T1-weighting (23Na-T1). (iii) An inversion recovery (23Na-IR) sequence was used to utmost suppress the sodium signal from extracellular or vasogenic edema. Furthermore, a potential influence of the temperature dependency of the sodium relaxation times was considered. Additionally, 1H-MRI was performed to examine potential lipomatous or edematous changes. - Results: - In HypoPP, all 23Na sequences showed significantly (P < 0.05) higher signal intensities compared with PC patients and healthy subjects. In muscles of PC patients, provocation induced a significant (P = 0.0007) increase (>20%) in the muscular 23Na-IR signal and a corresponding decrease of muscle strength. Additionally, a tendency to higher 23Na-T1 (P = 0.07) and 23Na-TSC (P = 0.07) signal intensities was observed. Provocation revealed no significant changes in 1H-MRI. In volunteers and in the contralateral, not cooled lower leg, there were no significant signal intensity changes after provocation. Furthermore, the 23Na-IR sequence allows for a suppression of signal emanating from intravascular sodium and vasogenic edema. - Conclusions: - Our results indicate that the 23Na-IR sequence allows for a weighting toward intracellular sodium. The combined application of the 23Na-TSC and the 23Na-IR sequence enables an improved analysis of pathophysiological changes that occur in muscles of patients with muscular channelopathies.
Gesehen am 15.09.2022